Complicações da blefaroplastia superior - Artioli, Silvana Schellini [UNESP]; Valezi, Vanessa Grandi [UNESP]; Passos, Walberto [UNESP] (Soc Brasileira Oftalmologia, 2012)
The blepharoplasty has been performed with great frequency due to the appreciation of aesthetic surgery. The complications related to this procedure are rare. This case report aims to emphasize complications that can occur. T.J.S.P., 45 years old, female, white, resident of Botucatu City, presented dermatocalase bilaterally. We opted to perform upper blepharoplasty bilateral, by removing skin and fat of the upper eyelid. In the postoperative period was observed left eyelid ptosis. We decided to reinsert the levator muscle of the left upper eyelid. One month after the ptosis correction, retraction was observed in both upper eyelid. The patient was then submitted to surgery for the correction of eyelid retraction by disinsertion of the muscle of Muller. Two months after this last surgery, the patient presented right eyelid ptosis and worsening of eyelid retraction to the left. New surgery for correction of the eyelid retraction was made, using free graft sclera for elongation of the left eyelid levator muscle, with good results.The authors presented a patient who underwent a blepharoplasty and developed ptosis in the post-operative period, followed by eyelid retraction. These two possibilities may occur as a complication of blepharoplasty and the surgeon must be careful to handle in an appropriate way, in order to get the result that the patient expects to have.
Superior eyelid blepharoplasty and complications
Keywords: Blepharoplasty/adverse effects; Plastic surgery; Case reports